2017
DOI: 10.23986/afsci.58936
|View full text |Cite
|
Sign up to set email alerts
|

Thermal energy use for dehumidification of a tomato greenhouse by natural ventilation and a system with an air-to-air heat exchanger

Abstract: The aim of the study was to estimate the amount of thermal energy used for dehumidification of a naturally ventilated tomato greenhouse and to estimate how mechanical ventilation with the use of a heat exchanger recovering heat from the exhaust to the supply air may decrease the energy use. Measured use of thermal energy in a naturally ventilated tomato greenhouse was compared to modelled values using Powersim® software. By the help of the model an estimation of the amount of energy used for dehumidification w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Chemometric techniques have become an important tool in modern analytical chemistry for designing experiments, achieving instrumental calibrations, and ascertaining the quality (precision, accuracy, and uncertainties) of analyses in a wide variety of chemical matrices (Miller and Miller, 2010;Verma, 2016). In food chemistry, many authors (e.g., Raco et al, 2015;Fernández et al, 2016;Giordani et al, 2016;Maslak and Nimmermark, 2017;Foereid, 2017) have used linear regression models. Furthermore, some other publications where the OLR model was applied are as follows: Moreno-Rivas et al (2016) in biosorption of cadmium from aqueous solution by baker's yeast; Borges et al (2017) in analysis of buffalo milk; Gómez-Favela et al (2017) in modelling of water absorption in chickpea seeds; Chaparro et al (2017) in selection of the process parameters and drying protectant to granulated bioproducts based on microorganisms; Fuentes-Ortega et al (2017) in study of the process variables of microencapsulation sesame oil by spray drying; Pérez-Grijalba et al (2017) in study of the bio-functionality properties of blackberry juice; and Xu et al (2017) in seasonal and annual variations of atmospheric Hg and Pb isotopes in Xi'an, China.…”
Section: Introductionmentioning
confidence: 99%
“…Chemometric techniques have become an important tool in modern analytical chemistry for designing experiments, achieving instrumental calibrations, and ascertaining the quality (precision, accuracy, and uncertainties) of analyses in a wide variety of chemical matrices (Miller and Miller, 2010;Verma, 2016). In food chemistry, many authors (e.g., Raco et al, 2015;Fernández et al, 2016;Giordani et al, 2016;Maslak and Nimmermark, 2017;Foereid, 2017) have used linear regression models. Furthermore, some other publications where the OLR model was applied are as follows: Moreno-Rivas et al (2016) in biosorption of cadmium from aqueous solution by baker's yeast; Borges et al (2017) in analysis of buffalo milk; Gómez-Favela et al (2017) in modelling of water absorption in chickpea seeds; Chaparro et al (2017) in selection of the process parameters and drying protectant to granulated bioproducts based on microorganisms; Fuentes-Ortega et al (2017) in study of the process variables of microencapsulation sesame oil by spray drying; Pérez-Grijalba et al (2017) in study of the bio-functionality properties of blackberry juice; and Xu et al (2017) in seasonal and annual variations of atmospheric Hg and Pb isotopes in Xi'an, China.…”
Section: Introductionmentioning
confidence: 99%
“…Natural ventilation can be considered as a passive cooling system since it is based on a greenhouse design that does not resort to the use of equipment. Many works have been carried out on natural greenhouse ventilation systems, which are controlled by the window openings at the side-wall and roof levels [68][69][70][71][72]. The researchers found that the climate of greenhouses is highly impacted by the rate of the air exchange through natural convection, which mainly depends on the area of the openings.…”
Section: Natural Ventilationmentioning
confidence: 99%
“…Accordingly, natural ventilation is not sufficient to maintain the desired climate and it becomes more energy intensive, especially in cold periods [5]. For instance, in Sweden and Spain, the energy consumption designed for greenhouse dehumidification via natural ventilation is estimated to be between 20 and 30% of the total energy consumption [5,71,73].…”
Section: Natural Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Maslak and Nimmermark [93], implementing an air-to-air heat exchanger for dehumidification reduced energy use in a closed greenhouse in Sweden by up to 17%.…”
Section: Effects Of the Closed Greenhouse On Energy Usementioning
confidence: 99%